Tìm x để 6B + 7 = 7x biết B=7+72+73+.....+71998
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\Leftrightarrow x+9=39\Leftrightarrow x=30\\ b,\Leftrightarrow73-x=69\Leftrightarrow x=4\\ c,\Leftrightarrow x+7=38\Leftrightarrow x=31\\ d,\Leftrightarrow x+4=178\Leftrightarrow x=174\\ e,\Leftrightarrow2\left(x-51\right)=16+20=36\Leftrightarrow x-51=18\Leftrightarrow x=69\\ f,\Leftrightarrow x-19=9\Leftrightarrow x=28\\ g,\Leftrightarrow4\left(x-3\right)=49-1=48\Leftrightarrow x-3=12\Leftrightarrow x=15\)
a) 45 - ( x + 9 ) = 6
45 - x = 6 + 9
45 - x = 15
x = 45 - 15
x = 30
b) 89 - ( 73 - x ) = 20
89 - x = 20 + 73
89 - x = 93
x = 93 - 89
x = 4
c) 198 - ( x + 4 ) = 120
198 - x = 120 + 4
198 - x = 124
x = 198 - 124
x = 74
d) ( x + 7 ) - 25 = 13
x - 25 = 13 + 7
x - 25 = 20
x = 20 + 25
x = 45
e) 2 ( x - 51 ) = 2.23 + 20
2 ( x - 51 ) = 64 + 20
2 ( x - 51 ) = 84
x - 51 = 84 - 2
x - 51 = 82
x = 82 + 51
x = 133
f) 450 : ( x - 19 ) = 50
450 : x = 50 - 19
450 : x = 41
x = 450 : 41
x = 24
a) \(58+7x=100\)
\(=>7x=100-58\)
\(=>7x=42\)
\(=>x=42:7\)
\(=>x=6\)
b) \(3x-7=28\)
\(=>3x=28+7\)
\(=>3x=35\)
\(=>x=35:3\)
\(=>x=\dfrac{35}{3}\)
c) \(x-56:4=16\)
\(=>x-14=16\)
\(=>x=16+14\)
\(=>x=30\)
d) \(101+\left(36-4x\right)=105\)
\(=>36-4x=105-101\)
\(=>36-4x=4\)
\(=>4x=36-4\)
\(=>4x=32\)
\(=>x=32:4\)
\(=>x=8\)
e) \(\left(x-12\right):12=12\)
\(=>x-12=12.12\)
\(=>x-12=144\)
\(=>x=144-12\)
\(=>x=132\)
f) \(\left(3x-2^4\right).7^3=2.7^4\)
\(=>3x-2^4=2.7^4:7^3\)
\(=>3x-16=2.7=14\)
\(=>3x=14+16\)
\(=>3x=30\)
\(=>x=30:3\)
\(=>x=10\)
i) \(\left(10+2x\right).4^{2011}=4^{2013}\)
\(=>10+2x=4^{2013}:4^{2011}\)
\(=>10+2x=4^2=16\)
\(=>2x=16-10\)
\(=>2x=6\)
\(=>x=6:2\)
\(=>x=3\)
\(#WendyDang\)
c) \(\left|x\right|=3,5\Rightarrow\left[{}\begin{matrix}x=3,5\\x=-3,5\end{matrix}\right.\)
d) \(\left|x\right|=-2,7\Rightarrow x\in\varnothing\)
l) \(\left|x+\dfrac{3}{4}\right|-5=-2\Rightarrow\left|x+\dfrac{3}{4}\right|=3\)
\(\Rightarrow\left[{}\begin{matrix}x+\dfrac{3}{4}=3\\x+\dfrac{3}{4}=-3\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=3-\dfrac{3}{4}\\x=-3-\dfrac{3}{4}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{9}{4}\\x=\dfrac{15}{4}\end{matrix}\right.\)
Đính chính câu l \(x=-\dfrac{15}{4}\) không phải \(x=\dfrac{15}{4}\)
a: =>7x=42
hay x=6
b: =>5x=35
hay x=7
c: =>x-14=16
hay x=30
d: =>36-4x=4
=>4x=32
hay x=8
e: =>x-12=144
hay x=156
f: =>3x-16=14
hay x=10
g: =>x+33=45
hay x=12
h: =>(x+9):2=39
=>x+9=78
hay x=69
a: =>7x=42
hay x=6
b: =>5x=35
hay x=7
c: =>x-14=16
hay x=30
d: =>36-4x=4
=>4x=32
\(1,\Leftrightarrow7x=42\Leftrightarrow x=6\\ 2,\Leftrightarrow36-4x=4\Leftrightarrow4x=32\Leftrightarrow x=8\\ 3,\Leftrightarrow3x=35\Leftrightarrow x=\dfrac{35}{3}\\ 4,\Leftrightarrow x-12=144\Leftrightarrow x=156\\ 5,\Leftrightarrow x-14=16\Leftrightarrow x=30\\ 6,\Leftrightarrow3x-24=\dfrac{148}{73}\Leftrightarrow3x=\dfrac{1900}{73}\Leftrightarrow x=\dfrac{1900}{219}\\ 7,\Leftrightarrow33+x=45\Leftrightarrow x=12\\ 8,Sai.đề\\ 9,\Leftrightarrow\left(x+9\right):2=39\Leftrightarrow x+9=78\Leftrightarrow x=69\\ 11,\Leftrightarrow2\left(x+7\right)=38\Leftrightarrow x+7=19\Leftrightarrow x=12\\ 13,\Leftrightarrow2\left(x-51\right)=66\Leftrightarrow x-51=33\Leftrightarrow x=84\)
\(15,\Leftrightarrow x-19=9\Leftrightarrow x=28\\ 17,\Leftrightarrow\left(x-3\right):2=48\Leftrightarrow x-3=96\Leftrightarrow x=99\\ 19,\Leftrightarrow0x=46\Leftrightarrow x\in\varnothing\\ 8,Sai.đề\\ 14,\Leftrightarrow2x=209\Leftrightarrow x=\dfrac{209}{2}\\ 16,\Leftrightarrow2x+6=157\Leftrightarrow2x=151\Leftrightarrow x=\dfrac{151}{2}\\ 18,\Leftrightarrow5\left(x+4\right)=100\Leftrightarrow x+4=20\Leftrightarrow x=16\\ 20,\Leftrightarrow\left(3x-5\right)^3=27=3^3\Leftrightarrow3x-5=3\Leftrightarrow x=\dfrac{8}{3}\)
B=7+72+...+71998
7B=72+73+...+71999
7B+7=7+72+...+71998+71999=B+71999
7B-B=71999-7
6B+7=71999
mà 6B+7=7x
nên x=1999
Vậy x=1999